IMPLEMENTASI MANAJEMEN LINGKUNGAN DALAM MEWUJUDKAN SEKOLAH ADIWIYATA - Tri Warsiati (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2018)
Abstract This research aims to find out about general: 1) implementation of physical environment management including planning, organizing, implementing, and evaluating; 2) supporting and inhibiting factors in physical environment management implementation; and 3) how to overcome the inhibition in physical environmental management in achieving adiwiyata school in MAN 2 Kulon Progo.This research is a descriptive qualitative method. The subjects of this research are the school residents who are involved in the program activities adiwiyata. The validity of the data uses triangulation and observational persistence. Data collecting technique in this research is interviews, observation, and documentation. Data analysis uses an interactive model of Miles and Huberman through activities of data collection, data reduction, data presentation, and making conclusion.The results of the research indicates that the implementation of physical environ mentmanagement has generally been carried out well. Key words: adiwiyata school, management, physical environment